Assessment of traumatic dental injuries in patients with cerebral palsy - A Dubey; P A Ghafoor; M Rafeeq (Wolters Kluwer Medknow Publications, 2015)
Background: Cerebral palsy is an umbrella term for a group of conditions characterized essentially by motor dysfunctions that may be associated with sensory or cognitive impairment. Such children tend to have a higher incidence of traumatic dental injuries than the general population. This increased incidence is often attributed to poor muscular co-ordination that predisposes individuals with Cerebral palsy to trauma Aim: The study was conducted to assess different dental injuries and the risk factors for dental trauma to occur in patients with cerebral palsy. Materials and Methods: The study comprised 70 children and adolescents with cerebral palsy attending special school in Durg and Bhilai city between 7 and 18 years of age. Results: Dentinal fracture was seen in 40% of cases. Few cases had tooth displacement, discoloration, and pulpal involvement. Conclusion: Dentists should be well aware of the possible dental injuries in such patients. Preventive measure measures should be taken by health care provider to reduce traumatic exposure.